2013
DOI: 10.1002/app.39758
|View full text |Cite
|
Sign up to set email alerts
|

Properties and phase segregation of crosslinked PCL‐based polyurethanes

Abstract: Polyurethane (PU) films were prepared from different types of poly(ε‐caprolactone) glycols and hexamethylene diisocyanate without using any other ingredients such as solvent, catalyst, or chain extender. Polymers were stabilized by crosslinking formed as allophanate and/or biuret linkages during the curing process. The effects of different components on the product properties such as chemical structure, microphase segregation, mechanical strength, thermo‐mechanical, thermal properties, and surface hydrophilici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…In the PU IR spectra, one can observe the absorption bands associated with a urethane group, such as the stretching vibrations of an amine group -NH at 3300 cm −1 [20]. The position of bands suggests that -NH groups are engaged in the formation of hydrogen bonds [21]. The double peak appearing at ca.…”
Section: Resultsmentioning
confidence: 99%
“…In the PU IR spectra, one can observe the absorption bands associated with a urethane group, such as the stretching vibrations of an amine group -NH at 3300 cm −1 [20]. The position of bands suggests that -NH groups are engaged in the formation of hydrogen bonds [21]. The double peak appearing at ca.…”
Section: Resultsmentioning
confidence: 99%
“…e absorption bands at 1725 and 1630 cm −1 are due to the vibration of C=O (carbonyl) groups in urethane bonds (I amide absorption band). e band at around 1585 cm −1 corresponds with N-H stretching vibration [31,32]. e bands in the 1150-950 cm −1 range from the ether C-O-C groups from PEG [33] are covered with bands related to PO 3− 4 groups from HA [34], but the bands in this range are broader than for pristine HA.…”
Section: Ftir and Xrd Analysis Of Ha-g-pegmentioning
confidence: 96%
“…The bands at 1532 cm −1 was attributed to the bending vibration of NH and the stretching vibration of CN which confirmed that urethane linkages were formed between OH in the HTWT and NCO. The band at 1710 to 1725 cm −1 which was observed in PUF1‐PUF4 was assigned to the carbonyl stretching of CO that was hydrogen bonded with the N‐H group of polyurethane . The bands at 1510 and 1596 cm −1 were derived from the aromatic rings of PMDI .…”
Section: Resultsmentioning
confidence: 99%
“…The first stage of degradation at 330 to 346 °C corresponded to breakage of the urethane bond. The second stage at 367 to 432 °C corresponded to the decomposition of the HTWT, and the third stage at 451 to 466 °C corresponded to the decomposition of the PCL diols …”
Section: Resultsmentioning
confidence: 99%